Behaviour and performance efficiency of solar air heater with impinging jets on corrugated plate - Aboghrara, Alsanossi Mohamed (2017)
Energy is a subject of vital importance because of our great dependence on it in all aspects of life including the social sphere, the economy, agricultural and industry. Solar energy is one of the most promising renewable energy sources in the world. Solar radiation has potential for drying purposes and space heating. Solar collectors are employed to convert incident solar radiation into thermal energy. Solar air heaters are extensively used due to minimal used of materials, simple design, less maintenance, less corrosion and few leakage problems. On the other hand, air type solar collectors have two inherent disadvantages, low thermal capacity of air and a low absorber to air heat transfer coefficient. Therefore, this research is motivated by the need to study and develop a new solar air heater. Thus, the primary objective of this study is to analyses the behavior of the solar air heater with jet impingement on a corrugated absorber plate and compares its performance efficiency with a conventional solar air heater by determine the factors affecting the performance of the SAH, than design, simulate, and validate experimentally the new novel design for the SAH, using indoor tests. Numerical and experimental analysis was used to achieve the aforementioned objective. Building the mathematical model of the proposed design using MATLAB software to predict the thermal performance of the SAH, followed by validation experimentally using indoor test. The results showed that the thermal performance of the solar air heater system with jet impingement on a flat plate absorber is better than the solar air heater cross corrugated plate without a jet however, the solar air heaters system with a jet impingement on corrugated plate have higher thermal performance efficiency of approximately 7%. The agreement between experimental results and predicted results was shown in most cases, of 500-1000 w/m2 solar radiation. Good agreement was achieved between the simulation and the experimental data. Thus, it can be concluded that the increment in solar air heaters efficiency is higher with the corrugated absorber due to addition vortexes, and because of reduced influence of the jet air velocity on the heat transfer coefficient at the lower flat absorber plate since the turbulence increases at the corrugated absorber for fixed mass flow rates of air and channel widths.